123 The impact of panel size on the yield of genetic testing in hypertrophic cardiomyopathy: a systematic review. (May 2019) - Quinn, Ellie; Howley, Dee; O'Mahony, Constantinos; Akhtar, Mohammed Majid; Savvatis, Konstantinos; Lopes, Luis; Funnell, Paula
Abstract : Introduction: Diagnostic genetic testing is an integral part of patient management in hypertrophic cardiomyopathy (HCM). Over time, the number of genes included in diagnostic genetic panels increased. The aim of the systematic review was to examine the impact of panel size on diagnostic yield. Methods: All cohort studies reporting the results of genetic testing in HCM patients were included, irrespective of setting. PubMed/Medline was searched from May 2000 (advent of next generation sequencing technology) to May 2018 using the following terms: (Hypertrophic Cardiomyopathy OR Hypertrophic Obstructive cardiomyopathy OR HCM OR HOCM) AND (Genotype OR Genetic Testing OR HCM panel OR pathogenic OR variant of unknown significance OR VUS OR Next Generation Sequencing OR Gene* Test* OR Genotyp*). The systematic review was carried out in accordance to the Preferred Reporting Items for Systematic reviews and Meta-Analyses amendment (PRISMA). Results: A total of 4837 articles fulfilled the search criteria in PubMed and 55 observational studies were included in the systematic review. Most study cohorts were derived from European countries (47%) and involved a single centre (73%). Prospective data collection was employed in 32 (58%) studies. The median cohort size was 124 patients (IQR 70–299). At least five studies included individuals ≤16 years of age (the minimum age was not reported in 47 (85%) studies). The studies tested 2 to 15 sarcomeric protein genes (median 8 genes; IQR: 5–10), including MYH7, MYBPC3, TNNT2, TNNI3, MYL2, MYL3, ACTC1, TPM1, TNNC1, MYH6, CSRP3, DES, TCAP, PDLIM3, PLN. All studies tested for mutations in MYBPC3 and MYH7 and most studies additionally included at least one of the following genes: TNNT2, TNNI3, MYL2, MYL3, ACTC1 and TPM1. The majority of positive mutations identified were in MYBPC3 (20%) and MYH7 (12%) (see figure 1). For all other sarcomeric genes, yield was <3%. Percentage yield varied greatly between studies with a range of 19–90% (mean 44%) and showed no discernible relationship with panel size (see figure 2). Conclusion: Over time, the number of genes included on HCM diagnostic genetic panels has increased but this has not translated to a significant improvement in diagnostic yield. Larger panels may introduce more complexity and uncertainty in the clinical setting and some of the high diagnostic yields may be explained by lax variant interpretation methods. Conflict of Interest: none